Imaging of patients with complex hemodialysis arterio-venous fistulas using time-resolved dynamic CT angiography: comparison with duplex ultrasound - Meyer, Mathias; Geiger, Nicole; Benck, Urs Tobias; Rose, Daniela; Janssen, Sonja; Meyer, Melissa; Schönberg, Stefan; Henzler, Thomas (Scientific reports, 2017)
To evaluate the feasibility and potential on therapy management of time-resolved dynamic computed tomography angiography (dCTA) in patients with forearm arterio-venous fistula (AVF)/arterio-venous grafts (AVG). Thirty-five patients with complex failing forearm AVF/AVGs were examined with ultrasound and a dCTA protocol. Diagnosis and therapy management was evaluated versus duplex ultrasound (DUS) in three different readouts: 1. all dCTA datasets; 2. one arterial phase of the dCTA dataset; 3. one arterial and one venous dataset out of the dCTA dataset. All reads were performed >30 days apart from each other. Using all data of the dCTA examination, 20 patients were classified as having a stenosis >50%, 12 high-shunt flow, 11 partial thrombosis, 5 venous aneurysms and 5 complete thrombosis of their AVF/AVG grafts. This lead to 13 additional pathologic findings not visible on DUS and reclassification as normal in one patient with suspected AVF stenosis and complete thrombus on DUS. These additional findings lead to a direct change of therapeutic management in 8 patients. Compared to readout 1 (53 pathologies), readout number 2 and 3 revealed only 33 and 41 pathologies, respectively. dCTA provides additional information, improving diagnostic confidence and leading to changes in therapy management when compared to DUS alone.